Assessing the Viability of Waste Tyre Rubber Powder as Additives in Rigid Polyurethane Insulation Foam - Chong Jin Phang; Hilmi Kosnin; Choy Man Kei; Mohd Syafiq Syazwan Mustafa; Fatimah Mohamed Yusop (Progress in Engineering Application and Technology, 2024)
The amount of waste generated throughout the entire world is rising yearly. Effective thermal insulation is one of the main qualities of a good insulation material. The aim of the research work is to investigate the potential of waste tyre rubber powder as an additive in insulation panel. In order to achieve the aim, produce insulation foam with different ratio of rigid polyurethane (RPU) and waste tyre rubber powder. Also, to investigate the relative effectiveness of rigid polyurethane and waste tyre rubber powder. Insulation foam with 10% WTR and RPU has the optimum performance and better proportion ratio as the modified content of insulation foam. The characteristic of insulation foam obtain from the testing is 0.19MPa, 0.23MPa and 0.0923W/m℃ respectively which proven an improvement in insulation foam by adding waste tyre rubber (WTR) powder with RPU.